Research on the Dynamic Behaviors of a Spar Floating Offshore Wind Turbine With an Innovative Type of Mooring System - Ma, Yuan; Chen, Chaohe; Fan, Tianhui; Lu, Hongchao (Frontiers in Energy Research, 2022)
Due to the existence of rotor and tower, the floating offshore wind turbine (FOWT) is subjected to greater wind heeling moment than the conventional floating platform, which would cause significant pitch motion and bring great challenge to the structural safety and power generating efficiency. Moreover, the dynamic cable used for power transmission is sensitive to the horizontal motion of floating platform. Thus, it is essential to inhibit the pitch and horizontal motions of FOWT. The FOWT is connected to the seabed by a mooring system to resist the motions, while the conventional mooring system mainly resists the horizontal motion. In this article, an innovative type of mooring system was proposed to resist the pitch and horizontal motions simultaneously, by dividing the fairleads into two groups at different depths. The motion responses and structural loads of FOWTs were calculated and compared under the effects of the conventional and innovative mooring systems. In addition, the restoring forces and moments of two mooring systems were also given to better verify the motion-inhibiting performances. According to the results, the innovative mooring system was able to significantly reduce the pitch and surge motions of FOWT.